2019
DOI: 10.1128/aem.01335-19
|View full text |Cite
|
Sign up to set email alerts
|

Novel Probiotic Mechanisms of the Oral Bacterium Streptococcus sp. A12 as Explored with Functional Genomics

Abstract: Health-associated biofilms in the oral cavity are composed of a diverse group of microbial species that can foster an environment that is less favorable for the outgrowth of dental caries pathogens, like Streptococcus mutans. A novel oral bacterium, designated Streptococcus A12, was previously isolated from supragingival dental plaque of a caries-free individual and was shown to interfere potently with the growth and virulence properties of S. mutans. In this study, we applied functional genomics to begin to i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 87 publications
(102 reference statements)
0
41
0
Order By: Relevance
“…Recently our group reported that part of the arsenal deployed by S. sp. A12, a health-associated commensal with probiotic properties, to compete with the caries pathogen S. mutans includes its ability to degrade peptide cell-cell signaling molecules [18,19]. In particular, incubation of synthetic CSP or XIP with only culture supernates alone of S. sp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently our group reported that part of the arsenal deployed by S. sp. A12, a health-associated commensal with probiotic properties, to compete with the caries pathogen S. mutans includes its ability to degrade peptide cell-cell signaling molecules [18,19]. In particular, incubation of synthetic CSP or XIP with only culture supernates alone of S. sp.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, incubation of synthetic CSP or XIP with only culture supernates alone of S. sp. A12 abolishes the peptides' activity via Sgc or PcfO, respectively [18,19]. We set out in this study to explore how ComRS signaling in S. mutans is altered during direct growth with these competitor species, conditions that should more closely mimic oral biofilms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…on December 13, 2020 by guest http://aem.asm.org/ Downloaded from 5 A strategy gaining acceptance to support the health of dental tissues is use of probiotics;…”
Section: Introductionmentioning
confidence: 99%